Morphological and histopathological studies of Thelandros chalcidae (Oxyuroidea: Pharyngodonidae) infecting Chalcides ocellatus from Egypt - Mona F. Fol (SpringerOpen, 2021)
Abstract Background Thelandros (Pharyngodonidae) is a gastrointestinal nematode parasite with a life cycle including lizards as main hosts. Thelandros chalcidae collected from the large intestine of the Egyptian ocellated skink, Chalcides ocellatus were described and illustrated by light and scanning electron microscopes. Seven out of fifteen (46.66%) of the examined lizards were found to be naturally infected. Also, host intestinal tissues were evaluated from hematoxylin/eosin-stained sections to describe any histopathological changes. Results Microscopic examinations revealed that the recovered pharyngodonid species characterized by mouth with triangular opening and surrounded by six simple lips, the cuticle had regular transverse annulations extending from the posterior margin of the lips to the end of the body. Male was cylindrical with distinct truncated posterior end and measured 1.59–1.86 (1.64 ± 0.10) long and 0.29–0.37 (0.32 ± 0.01) in maximum width at the level of mid-body. Female measured 1.72–2.43 (1.85 ± 0.2) long and 0.36–0.49 (0.42 ± 0.01) maximum width at the mid-body level, terminated posteriorly in a short, stout spike. Histological studies observed structural alterations represented by leukocytic infiltration, villi atrophy, and muscularis degeneration. These changes were indicative of inflammatory and degenerative reaction due to Thelandros chalcidae infection. Conclusion The present morphological study revealed that the recovered pharyngodonid species was Thelandros chalcidae causing pathological alterations in Chalcides ocellatus intestinal tissues.